#### Answer

$y ' = 4x^{2} - 1 + 2e^{x}$
$y'' = 8x +2e^{x}$

#### Work Step by Step

$y = \frac{4x^{3}}{3} -x + 2e^{x}$
$y ' = \frac{4(3)x^{3-1}}{3} - 1 + 2e^{x}$
$y ' = 4x^{2} - 1 + 2e^{x}$
$y'' = 8x^{2-1} - 0 +2e^{x}$
$y'' = 8x +2e^{x}$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$y ' = 4x^{2} - 1 + 2e^{x}$
$y'' = 8x +2e^{x}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.